Nerve and muscle microvasculitis in peripheral neuropathy: a remote effect of cancer?. Issue 9 (September 1986) - Vincent, D; Dubas, F; Hauw, J J; Godeau, P; Lhermitte, F; Buge, A; Castaigne, P
Abstract : In a series of 50 cases in which nerve and/or muscle microvasculitis was seen on biopsy, seven were associated with malignancy. In two cases, the cancer was found after the discovery of microvasculitis. All patients exhibited sensory-motor neuropathy, which was often painful and asymmetrical, with a progressive course. ESR and CSF protein levels were always elevated. Motor conduction velocity was slightly reduced in three cases, unmeasurable in one case, and normal in three. Cancers involved were adenocarcinoma in five cases (three prostate and two lung), Hodgkin's disease in one and immunoblastic lymphadenopathy in one. A thorough search for cancer should be performed when microvasculitis is seen in nerve or muscle biopsy specimens, especially when ESR and CSF protein levels are elevated.